Writing Ireland in the Latin chronicles and histories of early Plantagenet England - Hendley Rooney, Daryl (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2023)
This thesis offers a fresh examination of Latin writers' attitudes towards and depictions of Ireland, its affairs and its people in early Plantagenet England. Moving beyond the 'Geraldine paradigm' that has hitherto now influenced how we understand contemporary 'English' views of Ireland and the Irish in the historiography, this thesis argues that there was a variety of depictions and attitudes that ranged from contempt for aspects of Irish life to sympathy for their colonial experiences to admiration for Ireland's natural environment to more ambiguous and indifferent views. Taken together, this material shows that Ireland and the Irish were malleable constructs for contemporary Latin chroniclers and historians seeking to understand and record for posterity a past, present and future for the inhabitants of early Plantagenet England.
APPROVED
Keywords: Ireland; England; Plantagenet; Gerald of Wales; Chronicles; Histories; Attitudes; Perceptions; Irish; English; Identity